Efektivitas Penggunaan Edmodo Berbasis Project Based Learning untuk Meningkatkan Kemandirian Belajar Mahasiswa - Dwi Yuniasih Saputri (Equilibrium: Jurnal Pendidikan, 2021)
This study aims to analyze the effectiveness of using edmodo based on project-based learning to improve learning independence for Applied Science courses at PGSD. This research is an experimental study with a quasi experimental control design. The subjects of this study were the fourth semester PGSD undergraduate students of UNS which consisted of 65 students. The instrument used was the learning independence observation sheet and the pretest and posttest questions. Data analysis used Paired Sample T-test and the increase was calculated using gain normalization. The results showed that the project-based learning-based edmodo media was effectively used to increase student learning independence in Applied Science courses with a sig = 0.000 0.05. The normalization results of the gain are 0.81 so that the project-based learning-based edmodo media is included in the high criteria in increasing student learning independence in Applied Science courses in PGSD Study Program.